Comprehensive analysis of DNA methylation and gene expression of placental tissue in preeclampsia patients. (2nd January 2016) - Xuan, Jin; Jing, Zhang; Yuanfang, Zhu; Xiaoju, He; Pei, Li; Guiyin, Jin; Yu, Zeng
ABSTRACT: Objective : DNA methylation is an important epigenetic regulator of gene transcription, and is involved in many diseases, which has been researched recently. In this study, we aimed to investigate DNA methylation and gene expression in preeclampsia placenta. Preeclampsia has been observed in patients with molar pregnancy where a fetus is absent, which demonstrates that the placenta is sufficient to cause this condition. Methods : DNA methylation profiles and mRNA expression profiles were compared between two groups, six preeclampsia placentas and six normal pregnancy placentas using microarrays. Results : The number of promoters with altered DNA methylation was 1664. The number of mRNA identified as differentially expressed between the two groups of placenta samples were 1446. And the number of matched genes with a typical relationship between DNA methylation and gene expression was 42 hypomethylated DNA with increased mRNA expression and 19 hypermethylated DNA with decreased mRNA expression. The Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway and GO analysis were constructed based on the correlation between the differentially expressed DNA methylation and mRNAs. Conclusion: Our study is the first study to determine the genome-wide DNA methylation patterns in preeclampsia placenta using microarrays. The results revealed that clusters of DNA methylation were aberrantly altered in preeclampsia placenta compared with controls, which indicated misregulation of DNA methylation.